Pandemic Covid-19, Health Literature and Great Commission - Jolf John Tendean; Bartholomeus Diaz Nainggolan; Stimson Hutagalung (Sekolah Tinggi Teologi Baptis Indonesia, 2021)
The pandemic has disrupted all sectors, paralyzed and often stopped. Various efforts have been made to prevent the Covid-19 pandemic, but so far have not been completed. Large-Scale Social Restrictions were implemented, so that it also had an impact on religious activities in the church and also the activities of evangelistic missions. On this basis, the author conducted a study that aims to create a method of evangelism during the pandemic as an effort to fulfill the great commission. The method is to carry out a mission using health literature as a mission bridge. To get good research results, the author uses a literature study research method, where the author gets data from related literatures and processes it to get a conclusion. The result is that health literature becomes a very effective missionary bridge in accordance with the existing situation and conditions by making or printing tracts, magazines or books.